Verification and power consumption measurement of ‘eid signal in eddy stone beacon - bong Kim, Ki; mun Keum, Ki; bok Jang, Chang; Seok Kwon, Oh (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, users are receiving various services through smart phones. Especially, with the emergence of IoT, the service by collecting information from things is expanding, and various techniques for using BLE beacons are being studied.Methods/Statistical analysis: Services that use BLE beacons periodically transmit Bluetooth signals and mobile devices receive signals from near beacons. In this case, the mobile application should also periodically scan for the Bluetooth signal. It consumes additional power from the smartphone. Therefore, low power consumption is an important issue for services that use beacons. Optimized results should be found by measuring power at various levels of beacon scan period and beacon advertising period.Findings: As a result of this research, the power consumption exponentially increases as the scan period becomes shorter, but the beacon recognition rate does not improve significantly. The average power consumption was 9.6% at 10s Scan Period, but 6.5% at 30s and 5.6% at 100s. Advertising Period affected the change of Beacon Recognition Rate though the effect of power consumption was small. The Beacon Recognition Rate was very low when the Advertising Period was short, but it was 50% to 70% at 200ms to 1000ms. In the service used in this study, the scan period was set to 30 seconds and the advertisement period to 1000ms for optimization.Improvements/Applications: Applying the results of this paper to various beacons and services requires additional experimental design that takes into account beacons and other indicators that affect variables, such as scan execution time, signal strength, and beacon life.Â